Urdu English Foreign Language Learners Voices Learning English Online During the COVID-19 - Sana Khan, Sajjad Hussain, Ayman Riheel Alnaas Taha, Milad Salem Ebshara, Hafiz Ali Raza, Dina Chamidah, (Pakistan Journal of Medical & Health Sciences, 2022)
The unprecedented closure of institutions and schools due to the current epidemic has renewed interest in entirely online education. During the COVID-19 outbreaks, this survey aimed to discover how Urdu EFL students felt about online learning. Written reflections were used to collect qualitative data from 40 Pakistani undergraduate students majoring in English, with five of them selected for a semi-structured interview on purpose. Because it was regarded appropriate during the current epidemic, the student participants had positive attitudes toward online learning. However, according to qualitative data analysis, they preferred to learn English in face-to-face classrooms. In addition, an unstable internet connection, a lack of contact and teacher explanations, and potential distractions impeded their online English learning. Participants also made recommendations, and a debate was held on the educational implications.